2012
DOI: 10.22610/jebs.v4i4.320
|View full text |Cite
|
Sign up to set email alerts
|

Reasons of Tax Avoidance and Tax Evasion: Reflections from Pakistan

Abstract: Amount of taxes serves as life blood for government. This paper aims to recognize reasons/causes of tax avoidance and evasion in Pakistan. Relationship between variables of reasons/causes of tax avoidance and evasion are also examined. A questionnaire is developed after reviewing literature to collect responses. Data are analyzed using percentages, arithmetic mean, standard deviation, variance, central limit theorem, cumulative normal distribution calculator, factor analysis, and correlation technique. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
1
16
0
7
Order By: Relevance
“…These variables are in confirmation with findings of prior, small-scale tax evasion studies for Pakistan, too (Mughal and Akram, 2012;Awan and Hannan, 2014;Khan and Ahmad, 2014).…”
Section: Figure 1: Predictive Probabilities Of Treatment Assignment -supporting
confidence: 89%
“…These variables are in confirmation with findings of prior, small-scale tax evasion studies for Pakistan, too (Mughal and Akram, 2012;Awan and Hannan, 2014;Khan and Ahmad, 2014).…”
Section: Figure 1: Predictive Probabilities Of Treatment Assignment -supporting
confidence: 89%
“…The results indicated that tax evasion led to economic instability while increased tax revenues had the tendency of improving the economic situation of the 29 OECD countries. Mughal and Akram (2012) considered the causes of tax avoidance and evasion by using primary data gathered through administering of questionnaires using descriptive statistical tools, the results indicated that all variables representing the causes of tax evasion and avoidance in Pakistan were accurate and there was a 100% positive relationship among the study variables.…”
Section: Foreign Studiesmentioning
confidence: 99%
“…Universally, tax evasion is considered as a crime, which means it an unlawful act in a global context. However several reasons have been used to justify tax evasion in our contemporary times, such reasons include: high tax rates, illiteracy, lack of proper awareness, corruption in public offices, lack of adequate training for tax officials, embezzlement of tax revenues, loopholes in the tax laws, inability to interpret complex tax laws, weak legal framework and failure on the part of the judicial system to enforce relevant statutes against tax defaulters (Mughal and Akram, 2012;Adebisi & Gbegi, 2013;Obafemi, 2014;Onyeka & Nwankwo, 2016;Folayan & Adeniyi, 2018). In whichever scenario tax evasion occurs, it is usually harmful to an economy especially the evolving economies, in such a manner that development will keep dwindling.…”
Section: Introductionmentioning
confidence: 99%
“…The low taxpayers' awareness will create several problems, one of which is tax evasion [49]. Tax evasion in the research of [32] can be described as an act where taxpayers do not obey and purposefully violate the tax laws in order to run away from their responsibility to pay taxes. According to [41], included in tax evasions are calculating and reporting sales revenue to be lower than what it actually is, inflating transaction cost by creating fictitious transaction cost, fictitious export transactions and forging company's financial documents.…”
Section: Introductionmentioning
confidence: 99%